We cannot shrug off the shoulder seasons: addressing knowledge and data gaps in an Arctic headwater. (22nd September 2020) - Shogren, Arial J; Zarnetske, Jay P; Abbott, Benjamin W; Iannucci, Frances; Bowden, William B
Abstract: As environmental change in the Arctic accelerates, there is a growing need to accurately quantify the response of Arctic ecosystems throughout the year. To assess the temporal coverage of observations of carbon and nutrient fluxes, we used literature synthesis, quantitative meta-analysis, and exploration of a novel biogeochemical dataset from one of the best-documented Arctic ecosystems: the headwaters of the Kuparuk River in Northern Alaska. The meta-analysis of 204 peer-reviewed studies revealed a strong temporal gap in observations of biogeochemistry and hydrology of the Kuparuk River, with substantially fewer observations from the early and late 'shoulders' of the thaw season (defined as the period before snowmelt or after plant senescence). To test and illustrate how much this bias might influence fundamental ecosystem level measurements, such as riverine carbon and nutrient fluxes, we used high-frequency, in-situ water chemistry sensors to estimate riverine export budgets across the thaw season for dissolved organic carbon (DOC) and nitrate (NO3 − ) in the Kuparuk headwaters. With this novel dataset, we found that a large proportion (∼30%) of the annual export of DOC and NO3 − occurred during the shoulder seasons, which are not well characterized even for this well-documented Arctic system. These analyses raise the broader question: what ecological information are we missing by giving these seasons the 'cold shoulder'? As climate change alters seasonality, filling this major data gap in the shoulder seasons is crucial to understand the response of Arctic ecosystems.